1995
DOI: 10.1101/gad.9.17.2143
|View full text |Cite
|
Sign up to set email alerts
|

The WT1 gene product stabilizes p53 and inhibits p53-mediated apoptosis.

Abstract: The Wilms' tumor-suppressor gene product WT1 coimmunoprecipitates with p53 from baby rat kidney (BRK) cells and Wilms' tumor specimens, and expression of WT1 in BRK cells is associated with increased levels of endogenous wild-type p53 protein. To study the effect of WT1 on p53 function, we cotransfected expression constructs into Saos-2 cells, an osteosarcoma cell line without endogenous expression of either gene. Expression of WT1 resulted in increased steady-state levels of p53, attributable to a prolongatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
0
2

Year Published

1997
1997
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(177 citation statements)
references
References 71 publications
4
171
0
2
Order By: Relevance
“…Thus, modulation of RB and E2F through p53 signalling in response to DNA damage may play a central role in deciding the choice between cell cycle and arrest. Moreover, it has been shown that the Wilms tumor suppressor gene product, WT1, binds p53 and inhibits p53-dependent apoptosis without a ecting p53-dependent growth arrest, also revealing a determining mechanism for p53 downstream events (Maheswaran et al, 1995).…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…Thus, modulation of RB and E2F through p53 signalling in response to DNA damage may play a central role in deciding the choice between cell cycle and arrest. Moreover, it has been shown that the Wilms tumor suppressor gene product, WT1, binds p53 and inhibits p53-dependent apoptosis without a ecting p53-dependent growth arrest, also revealing a determining mechanism for p53 downstream events (Maheswaran et al, 1995).…”
Section: Role Of P53 In Growth Arrestmentioning
confidence: 99%
“…These results have two implications: (i) they argue that the integrity of WT1 zinc ®nger I is essential in maintaining par-4 interaction, and (ii) the abolishment of par-4 binding to EWS/WT1 may contribute to the oncogenic potential of this fusion product, since par-4 binding to EWS/WT1 could be expected to prevent activation by the NTD-EWS domain. The p53 gene product can also associate with WT1 via its zinc ®ngers (Maheswaran et al, 1995). We have not assessed whether this association is maintained with EWS/WT1 chimeric products, but its disruption could also be important to the mechanism of transformation by EWS/WT1.…”
Section: Discussionmentioning
confidence: 99%
“…Stable cell lines expressing adenovirus 5 E1A (6.1 cells) and E1A plus E1B (10.2 cells) have been described elsewhere (Haber et al, 1992;Maheswaran et al, 1993Maheswaran et al, , 1995. To map the WT1 interaction domains, 10.2 cells were stably transfected by calcium phosphate transfection with CMV-driven, HA-tagged WT1 deletion constructs, which have been previously described .…”
Section: Cell Lines Transfections and Expression Constructsmentioning
confidence: 99%